Copper metallurgy at the crossroads - Habashi F. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Copper technology changed from the vertical to the horizontal furnace and from the roast reaction to converting towards the end of the last century. However, the horizontal furnace proved to be an inefficient and polluting reactor. As a result many attempts were made to replace it. In the past 50 years new successful melting processes were introduced on an industrial scale that were more energy efficient and less polluting. In addition, smelting and converting were conducted in a single reactor in which the concentrate was fed and the raw copper was produced. The standing problem in many countries, however, is marketing 3 tonnes of sulfuric acid per tonne of copper produced as well as emitting large amounts of excess SO2 in the atmosphere. Pressure hydrometallurgy offers the possibility of liberating the copper industry from SO2 problem. Heap leaching technology has become a gigantic operation. Combined with solvent extraction and electrowinning it contributes today to about 20% of copper production and is expected to grow. Pressure leaching offers the possibility of liberating the copper industry from SO2 problem. The technology is over hundred years old. It is applied for leaching a variety of ores and concentrates. Hydrothermal oxidation of sulfide concentrates has the enormous advantage of producing elemental sulfur, hence solving the SO2 and sulfuric acid problems found in smelters. Precipitation of metals such as nickel and cobalt under hydrothermal conditions has been used for over 50 years. It has the advantage of a compact plant but the disadvantage of producing ammonium sulfate as a co-product. In case of copper, however, precipitation takes place without the need of neutralizing the acid, which is a great advantage and could be an excellent substitute for electrowinning which is energy intensive and occupies extensive space. Recent advances in the engineering aspects of pressure equipment design open the door widely for increased application. .